Educational Content Development to Enhance STEM Learning - Dávila Guzmán, Nancy Elizabeth; Tiempos Flores, Norma; Maya Treviño, María de Lourdes; Sánchez Vázquez, Astrid Iriana; Cerino Córdova, Felipe de Jesús (Kassel University Press, 2019)
In this study, multidisciplinary teams were formed to develop educational content as digital videos to help in the learning process in Science, Tech-nology, Engineering and Mathematics (STEM) education. The usefulness of the web-learning tool was evaluated by surveys and tests taken by chemical engineering freshman students. The results showed that these students’ scores were higher than the scores obtained by students of previous courses where the web-learning tool was not employed. On the other hand, the au-dience analysis indicated that the average age is 18-24 (91.2%) and the gen-der distribution was 54.9% male and 46.6% female from different countries (Mexico, Colombia, Spain, U.S., among others).